Tourism Development and Strategy for Increasing Numbers of Visitors in Kediri - Azizah, Anisah (Graduate School, Universitas Brawijaya, 2017)
Tourism is one source of local revenue. The key to improve quality of tourism destination is effective strategy to develop tourism sectors. To develop tourism sector, one should emphasize on adequate maintenance of tourism destination and management. Studies have been conducted in Kediri analyzing how potential the area was for tourism destination. It was expected that number of visitors and local revenue would increase by describing both internal and external factors supporting the tourism sector in the area. The study was a descriptive study that employed mixed methods (quantitative and qualitative). The data analysis methods were SWOT analysis followed by weighing using IFAS-EFAS analysis. The findings were (a) the government of Kediri should build shopping center that highlighted the local wisdom and more shopping centers more particularly in tourist destination that had no